The use of commercial mediation as alternative dispute resolution tool in the Czech Republic, Hungary and Slovakia - Poór, József; Lankašová, Radka; Engle, Allen D.; Szabó, Katalin; Budavári-Takács, Ildikó; Šeben, Zoltán; Korényi, Róbert; Szitás, Péter; Juhász, Tímea (Anali Ekonomskog fakulteta u Subotici, 2021)
For a long time, various companies and organizations have used traditional courts or other legal tools to resolve different complex disputes or problems. However, numerous influencing factors often interrupted this formalized problem-solving approach. In the countries of the former Eastern bloc, under the former communist system, the Party often acted as mediator. This, of course, has changed totally since the political system has become democratic. Our study investigates conflict-solving styles, procedures and processes in Central Europe – the Czech Republic, Slovakia and Hungary. The study done in 297 companies in these three countries show that conflicts between individuals, employees and the company are found most often, while problems between the local company and associated parent companies are less frequently found. Regardless of the country, companies have spent at least 10% of their working time dealing with internal conflicts. Some 79% of organizations focus on managing external conflicts for at least 10% of their working time, while around 9% of companies use mediation as a method of resolving conflict. The organizations in the study do not differ from country to country in terms of the use and success of mediation practices.